The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/09638180.2021.1919169
|View full text |Cite
|
Sign up to set email alerts
|

The Sheep Watching the Shepherd: Employee Representation on the Board and Earnings Quality

Abstract: We investigate to what degree employee representatives contribute to the board's monitoring of earnings quality. We argue that employee representatives have incentives to prevent earnings manipulations motivated by negotiation considerations. Furthermore, they seek risk reducing policies, have a long-term interest in their firm and possess firm-specific knowledge, which in turn can result in improved earnings quality. Employee representation also increases the diversity on the board, which can enhance the boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…Instead, it is considered to take place in loose networks of social interactions between actors, which address mutual interests (Latour 1987). ANT may therefore be a useful tool for studying AHR networks, and can compensate for some of the drawbacks of legitimacy theory, which favours specific stakeholders (Parker 2005). It may provide insights into the process required to create knowledge and network dynamics and achieve common objectives (Chua 1995).…”
Section: Critical Evaluation and Discussionmentioning
confidence: 99%
“…Instead, it is considered to take place in loose networks of social interactions between actors, which address mutual interests (Latour 1987). ANT may therefore be a useful tool for studying AHR networks, and can compensate for some of the drawbacks of legitimacy theory, which favours specific stakeholders (Parker 2005). It may provide insights into the process required to create knowledge and network dynamics and achieve common objectives (Chua 1995).…”
Section: Critical Evaluation and Discussionmentioning
confidence: 99%
“…In other words, the problem of adverse selection arising from the advantage of information becomes an essential factor for some enterprises to defeat the original purpose of the government's innovation incentive policy. Some studies found an internal drive to manipulate R&D investment for tax incentive reduction and expectation adjustment (Overland & Samani, 2021;Liu, et al, 2021). Overall, it is essential to understand and explore the motivations for corporate R&D manipulation to help drive the implementation of "genuine innovation" towards a virtuous cycle.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Even though many companies reportedly consider employee involvement as a positive aspect of organisational development, implementation is usually problematic because of the lack of a meaningful agenda (“why we are involving employees?”) and underdeveloped means (“how we are doing so?”) (Overland & Samani, 2021; Rees et al, 2013). From an accountability perspective, workplace democracy begins by providing employees with instruments to control organisational conduct and hold managerial power to account (Battilana & Casciaro, 2021; Warren, 2014).…”
Section: Accountability and A Democratic Workplace Setupmentioning
confidence: 99%
“…and underdeveloped means ("how we are doing so?") (Overland & Samani, 2021;Rees et al, 2013). From an accountability perspective, workplace democracy begins by providing employees with instruments to control organisational conduct and hold managerial power to account (Battilana & Casciaro, 2021;Warren, 2014).…”
Section: Accountability and A Democratic Workplace Setupmentioning
confidence: 99%